2017
DOI: 10.4103/0366-6999.204113
|View full text |Cite
|
Sign up to set email alerts
|

Programmed Cell Death-1/Programmed Death-ligand 1 Pathway

Abstract: Objective:Sepsis remains a leading cause of death in many Intensive Care Units worldwide. Immunosuppression has been a primary focus of sepsis research as a key pathophysiological mechanism. Given the important role of the negative costimulatory molecules programmed cell death-1 (PD-1) and programmed death-ligand 1 (PD-L1) in the occurrence of immunosuppression during sepsis, we reviewed literatures related to the PD-1/PD-L1 pathway to examine its potential as a new target for sepsis treatment.Data Sources:Stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 80 publications
(112 reference statements)
0
15
0
Order By: Relevance
“…First, we performed flow cytometry analyses of PD-L1 surface expression. PD-L1 binding of PD-1 on T cells suppresses T cell proliferation ( 12 , 33 ) according to recent publications mainly through inhibiting the CD28 costimulatory pathway ( 34 ). The histogram overlay and associated quantification show that amiR cluster treatment resulted in significantly less PD-L1 expression on R848-stimulated suppressive APCs (Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, we performed flow cytometry analyses of PD-L1 surface expression. PD-L1 binding of PD-1 on T cells suppresses T cell proliferation ( 12 , 33 ) according to recent publications mainly through inhibiting the CD28 costimulatory pathway ( 34 ). The histogram overlay and associated quantification show that amiR cluster treatment resulted in significantly less PD-L1 expression on R848-stimulated suppressive APCs (Figure 4 C).…”
Section: Resultsmentioning
confidence: 99%
“…Although the range of tolerogenic/suppressive APCs is broad, some of the conducted immune inhibitory reactions appear to be universal and thus looked upon checkpoint mechanisms. Besides anti-inflammatory cytokine effects, inhibitory checkpoint mechanisms include programmed death-ligand 1 (PD-L1) binding to programmed cell death 1 (PD-1) on T cells ( 10 12 ) and modulation through indolamin-2,3-dioxygenase (IDO)-catalyzed tryptophan metabolites ( 13 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, COVID-19 management should aim to reverse immunosuppression and prevent resultant opportunistic infections. Previous studies on the mechanism of immunosuppression during sepsis have implicated overexpression of programmed death-1 (PD-1), an immune checkpoint, and its ligand known as programmed death ligand-1 (PDL-1) ( 52 ). Overexpression of other immune checkpoints, such as cytotoxic T-lymphocyte antigen-4 and B- and T- lymphocyte attenuator, is also known to drive immune suppression ( 53 ).…”
Section: Approaches For Managing Severe Covid-19: Lessons From Sepsismentioning
confidence: 99%
“…Furthermore, downregulation of HLA-DR, accelerated lymphocyte death or exhaustion, and clonal expansion of anti-inflammatory cells are all known correlates of immunesuppression during sepsis (53)(54)(55). Interestingly, blocking the immune checkpoints, particularly, PD-1/ PDL-1, has been shown to restore immune competence, howbeit, preclinically (52,53). Hence, these important immune-checkpoints remain attractive therapeutic targets that should be investigated for COVID-19 management.…”
Section: Immunosuppressionmentioning
confidence: 99%
“…In recent years, increasing studies such as those of Liu et al [ 31 ] and Sherwood et al [ 4 ] have demonstrated that PD-1/PD-L1 blockade could be used to treat sepsis. However, their studies focused on the mechanism of action.…”
Section: Discussionmentioning
confidence: 99%